The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Reply to Koller and Schobersberger: Comment on: "Revised Approach to the Role of Fatigue in Anterior Cruciate Ligament Injury Prevention: A Systematic Review with Meta-analyses". - Benjaminse, A; Webster, KE; Gokeler, A (Sports Med)

Correction to: Principles of Motor Learning to Support Neuroplasticity After ACL Injury: Implications for Optimizing Performance and Reducing Risk of Second ACL Injury. - Gokeler, A; Neuhaus, D; Benjaminse, A; Grooms, DR; Baumeister, Jochen (Sports Med)

Principles of Motor Learning to Support Neuroplasticity After ACL Injury: Implications for Optimizing Performance and Reducing Risk of Second ACL Injury. - Gokeler, Alli; Neuhaus, D; Benjaminse, A; Grooms, DR; Baumeister, Jochen (Sports Med)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Revised Approach to the Role of Fatigue in Anterior Cruciate Ligament Injury Prevention: A Systematic Review with Meta-Analyses - Benjaminse, Anne; Webster, Kate E.; Kimp, Alexander; Meijer, Michelle; Gokeler, Alli (Sports Medicine)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Realistic g (2) measurement of a PDC source with single photon detectors in the presence of background - Eckstein, Andreas; Christ, Andreas; Mosley, Peter J.; Silberhorn, Christine (physica status solidi c)
Keywords: Condensed Matter Physics

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Electronic structure and effective masses in strained silicon - Bouhassoune, Mohammed; Schindlmayr, Arno (Physica Status Solidi C)
The structural and electronic properties of strained silicon are investigated quantitatively with ab initio computational methods. For this purpose we combine densityfunctional theory within the local‐density approximation and the GW approximation for the electronic self‐energy. From the variation of the total energy as a function of applied strain we obtain the elastic constants, Poisson ratios and related structural parameters, taking a possible internal relaxation fully into account. For biaxial tensile strain in the (001) and (111) planes we then investigate the effects on the electronic band structure. These strain configurations occur in epitaxial silicon films grown on SiGe templates along different crystallographic directions. The tetragonal deformation resulting from (001) strain induces a valley splitting that removes the sixfold degeneracy of the conduction‐band minimum. Furthermore, strain in any direction causes the band structure to warp. We present quantitative results for the electron effective mass, derived from the curvature of the conduction band, as a function of strain and discuss the implications for the mobility of the charge carriers. The inclusion of proper self‐energy corrections within the GW approximation in our work not only yields band gaps in much better agreement with experimental measurements than the localdensity approximation, but also predicts slightly larger electron effective masses.

Do we know the band gap of lithium niobate? - Thierfelder, Christian; Sanna, Simone; Schindlmayr, Arno; Schmidt, Wolf Gero (Physica Status Solidi C)
Given the vast range of lithium niobate (LiNbO3) applications, the knowledge about its electronic and optical properties is surprisingly limited. The direct band gap of 3.7 eV for the ferroelectric phase – frequently cited in the literature – is concluded from optical experiments. Recent theoretical investigations show that the electronic band‐structure and optical properties are very sensitive to quasiparticle and electron‐hole attraction effects, which were included using the GW approximation for the electron self‐energy and the Bethe‐Salpeter equation respectively, both based on a model screening function. The calculated fundamental gap was found to be at least 1 eV larger than the experimental value. To resolve this discrepancy we performed first‐principles GW calculations for lithium niobate using the full‐potential linearized augmented plane‐wave (FLAPW) method. Thereby we use the parameter‐free random phase approximation for a realistic description of the nonlocal and energydependent screening. This leads to a band gap of about 4.7 (4.2) eV for ferro(para)‐electric lithium niobate.

Ab initiog-tensor calculation for paramagnetic surface states: hydrogen adsorption at Si surfaces - Gerstmann, Uwe; Rohrmüller, M.; Mauri, F.; Schmidt, Wolf Gero (physica status solidi (c))

Optical anisotropy of Si(111)-(4 × 1)/(8 × 2)-In nanowires calculated fromfirst-principles - Wippermann, S.; Schmidt, Wolf Gero; Bechstedt, F.; Chandola, S.; Hinrichs, K.; Gensch, M.; Esser, N.; Fleischer, K.; McGilp, J. F. (physica status solidi (c))

GaN growth on LiNbO3 (0001) - a first-principles simulation - Sanna, Simone; Schmidt, Wolf Gero (physica status solidi (c))

Temperature dependent stability of self-assembled molecular rows - Blankenburg, S.; Schmidt, Wolf Gero (physica status solidi (c))

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initio investigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, G. (physica status solidi (c))

Non-polar cubic AlGaN/GaN HFETs grown by MBE on Ar+implanted 3C-SiC (001) - Tschumak, Elena; Lindner, Jörg; Bürger, M.; Lischka, K.; Nagasawa, H.; Abe, M.; As, Donald (physica status solidi (c))
The growth of cubic group III-nitrides is a direct way to eliminate polarization effects, which inherently limit the fabrication of normally-off heterojunction field-effect transistors (HFETs) in GaN technology. HFET structures were fabricated of non-polar cubic AlGaN/GaN hetero layers grown by plasma assisted molecular beam epitaxy (MBE) on free standing 3C-SiC (001). The electrical insulation of 3C-SiC was realised by Ar+ implantation before c-AlGaN/GaN MBE. The structural properties of the epilayers were studied by highresolution x-ray diffraction (HRXRD). HFETs with normally off and normally-on characteristics were fabricated of cubic AlGaN/GaN. Capacitance-voltage (CV) characteristics of thegate contact were performed to detect the electron channel at the c-AlGaN/GaN hetero interface.

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initioinvestigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initioinvestigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, Guido (physica status solidi (c))

Time-resolved photoluminescence study of mesoporous ZnO nanostructures - Schwalm, Michael; Horst, Swantje; Chernikov, Alexej; Rühle, Wolfgang W.; Lautenschläger, Stephan; Klar, Peter J.; Meyer, Bruno K.; Waitz, Thomas; Tiemann, Michael; Chatterjee, Sangam (physica status solidi (c))
We report a systematic study of the photoluminescence properties of ZnO nanostructures. In particular, mesoporous ZnO powders of varying surface-to-mass ratio are investigated and compared to a bulk reference. At low temperatures the emission from higher-energy states is very pronounced and even dominant for samples with high surface-to-mass ratio.

Determination of homogeneous and inhomogeneous broadenings of quantum-well excitons by 2DFTS: An experiment-theory comparison - Kuznetsova, Irina; Thomas, Peter; Meier, Torsten; Zhang, Tianhao; Cundiff, Steven T. (physica status solidi (c))
The recently developed two-dimensional Fourier-Transform-Spectroscopy (2DFTS) in the optical regime has been established as an elegant experiment, which has manifold of applications in the investigation of semiconductor nanostructures. Here we focus on the real and imaginary part 2DFT spectra. As predicted recently, using rephasing and non-rephasing modes, we are able to determine the homogeneous and inhomogeneous broadenings of coupled excitonic resonances even for weak disorder where photon-echo data are not useful. Computed real and imaginary parts of the 2DFTS for rephasing and non-rephasing modes are compared with experimental data of a GaAs quantum well. It is demonstrated, that phase sensitive data for the rephasing and non-rephasing modes are able to accurately provide the disorder induced broadening in a complex coupled system for each transition separately.

Microscopic analysis of high-harmonic generation in semiconductor nanostructures - Golde, Daniel; Meier, Torsten; Koch, Stephan W. (physica status solidi (c))
A microscopic analysis of the emitted radiation of a semiconductor nanostructure after excitation with an extremely intense ultrashort laser pulse is presented. It is shown that the extreme nonlinear optical response is not sufficiently described by pure interband transitions but one has to include intraband effects as well. Numerical solutions of extended Bloch equations that include the coupled inter- and intraband dynamics are presented. For large excitation intensities, the intraband effects strongly modify the polarization dynamics and lead to a strong enhancement of high-harmonic generation compared to pure interband dynamics.

Theoretical study of phononassisted singlet-singlet relaxation in two-electron semiconductor quantum dot molecules - Grodecka, Anna; Machnikowski, Paweł; Förstner, Jens (physica status solidi (c))
Phonon-assisted singlet-singlet relaxation in semiconductor quantum dot molecules is studied theoretically. Laterally coupled quantum dot structures doped with two electrons are considered. We take into account interaction with acoustic phonon modes via deformation potential and piezoelectric coupling. We show that piezoelectric mechanism for the considered system is of great importance and for some ranges of quantum dot molecule parameters is the dominant contribution to relaxation. It is shown that the phonon-assisted tunneling is much faster (down to ∼ 6 ps even at zero temperature) in comparison with other decoherence processes. The influence of Coulomb interaction is discussed and its consequences are indicated. We calculate the relaxation rates for GaAs quantum dot molecules and study the dependence on quantum dot size, distance and offset between the constituent quantum dots. In addition the temperature dependence of the tunneling rates is analyzed.
Keywords: tet_topic_qd

1.5 µm luminescence from InAs/GaxIn1–xNyAs1–y quantum dots grown on GaAs substrate - Richter, M.; Hugues, M.; Damilano, B.; Massies, J.; Duboz, J.-Y.; Reuter, Dirk; Wieck, A. D. (physica status solidi (c))

Electron spin coherence in singly charged (In,Ga)As/GaAs quantum dots - Greilich, A.; Oulton, R.; Zhukov, E. A.; Yugova, I. A.; Yakovlev, D. R.; Bayer, M.; Shabaev, A.; Efros, Al. L.; Merkulov, I. A.; Stavarache, V.; Reuter, Dirk; Wieck, A. (physica status solidi (c))

Interplay of electron-phonon and Coulomb interaction in semiconductor quantum dots - Förstner, Jens; Knorr, A.; Moloney, J. V. (physica status solidi (c))
We theoretically study the biexciton-phonon interaction in strongly confined semiconductor quantum dots. For spectrally narrow single-pulse excitation generation of biexcitonic occupations is only possible via a two-photon cascade, which exhibits renormalized Rabi oscillations and spectrally compressed phononsidebands.
Keywords: tet_topic_qd

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Waveguide-plasmon polaritons in photonic crystal slabs with metal nanowires - Tikhodeev, S. G.; Gippius, N. A.; Christ, A.; Zentgraf, Thomas; Kuhl, J.; Giessen, H. (physica status solidi (c))

Observation of high Q resonant modes in optically pumped GaN/InGaN microdisks fabricated using photoelectrochemical etching - Haberer, E. D.; Meier, Cedrik; Sharma, R.; Stonas, A. R.; DenBaars, S. P.; Nakamura, S.; Hu, E. L. (physica status solidi (c))

Single quantum dot nano-LEDs - spectroscopy of an electrically controlled few-particle system - Schmidt, R.; Scholz, U.; Vitzethum, M.; Fix, R.; Malzer, S.; Metzner, C.; Kailuweit, P.; Reuter, Dirk; Wieck, A.; Hübner, M. C.; Stufler, S.; Zrenner, A.; et al. (physica status solidi (c))

Fano resonances in semiconductor quantum dots - Fühner, C.; Keyser, U. F.; Haug, R. J.; Reuter, Dirk; Wieck, A. D. (physica status solidi (c))

Pulse propagation in Bragg-resonant multiple quantum wells: from pulse breakup to compression - Nielsen, N. C.; Kuhl, J.; Schaarschmidt, M.; Förstner, Jens; Knorr, A.; Koch, S. W.; Gibbs, H. M.; Khitrova, G.; Giessen, H. (physica status solidi (c))
The nonlinear propagation of subpicosecond pulses resonant to the hh 1s exciton in Bragg-periodic multiple quantum wells is investigated experimentally and theoretically. We show coherent pulse breakup and its suppression for increasing pulse intensity in good agreement with calculations based on the semiconductor Maxwell-Bloch equations. For highly nonlinear excitation, pulse compression is observed which is strongly enhanced by the additional contribution of self-phase modulation in the barrier and substrate material.
Keywords: tet_topic_qw

Self-induced transparency in InGaAs quantum dot waveguides - Schneider, S.; Borri, P.; Langbein, W.; Woggon, U.; Förstner, Jens; Knorr, A.; Sellin, R. L.; Ouyang, D.; Bimberg, D. (physica status solidi (c))
We present the experimental observation and the theoretical modelling of self-induced transparency signatures such as nonlinear transmission, pulse retardation and reshaping for subpicosecond pulse propagation in a 2 mm-long InGaAs quantum-dot ridge waveguide at 10 K. The measurements were obtained using a cross-correlation frequency resolved optical gating technique which allows us to retrieve the field amplitude of the propagating pulses.
Keywords: tet_topic_qd

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)